Ion-specific modulation of interfacial interaction potentials between solid substrates and cell-sized particles mediated via zwitterionic, super-hydrophilic poly(sulfobetaine) brushes - Higaki, Yuji; Fröhlich, Benjamin; Tanaka, Motomu (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2017)
Zwitterionic polymer brushes draw increasing attention not only because of their superhydrophilic, self-cleaning capability but also due to their excellent antifouling capacity. We investigated the ion-specific modulation of the interfacial interaction potential via densely packed, uniform poly(sulfobetaine) brushes. The vertical Brownian motion of a cell-sized latex particle was monitored by microinterferometry, yielding the effective interfacial interaction potentials V(Δh) and the autocorrelation function of height fluctuation. The potential curvature V″(Δh) exhibited a monotonic increase according to the increase in monovalent salt concentrations, implying the sharpening of the potential confinement. An opposite tendency was observed in CaCl2 solutions, suggesting that the ion specific modulation cannot be explained by the classical Hofmeister series. When the particle fluctuation was monitored in the presence of free sulfobetaine molecules, the increase in [sulfobetaine] resulted in a distinct increase in hydrodynamic friction. This was never observed in all the other salt solutions, suggesting the interference of zwitterionic pairing of sulfobetaine side chains by the intercalation of sulfobetaine molecules into the brush layer. Furthermore, poly(sulfobetaine) brushes exhibited a very low V″(Δh) and hydrodynamic friction to human erythrocytes, which seems to explain the excellent blood repellency of zwitterionic polymer materials.
Publication date (web): January 25, 2017
Gesehen am 19.06.2018